2019
DOI: 10.2478/pjmpe-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study on the gold and gadolinium nanoparticles radio-sensitizer effect in the prostate 125I seeds radiotherapy

Abstract: Monte Carlo and TL dosimetry applied to the characterization of 125I brachytherapy with a different design with other 125I seeds. In a water phantom, lattice configuration simulated with 125I seed in the center and 10 nm gold and gadolinium nan-particle filed voxels. This simulation conducted to the characterization of the nano-particles DEF in low energy and prostate tissue. To study of the prostate brachytherapy, a humanoid computational phantom developed by CT slices applied. KTMAN-2 computational phantom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Application of nanoparticles in medical radiation physics, medical imaging, and radiation therapy of cancer has been reported by enormous studies. [1][2][3][4][5][6][7][8][9][10] Several nanoparticles have been used and studied for application in nanoparticle-aided radiation therapy (NART) with the photons in the energy range of tens to hundreds of keV. 2,5,[11][12][13][14][15][16][17] The studies showed that photoelectrons produced through photoelectric interaction of photons with high Z atoms of nanoparticles are the major players in the extra dose delivered around the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of nanoparticles in medical radiation physics, medical imaging, and radiation therapy of cancer has been reported by enormous studies. [1][2][3][4][5][6][7][8][9][10] Several nanoparticles have been used and studied for application in nanoparticle-aided radiation therapy (NART) with the photons in the energy range of tens to hundreds of keV. 2,5,[11][12][13][14][15][16][17] The studies showed that photoelectrons produced through photoelectric interaction of photons with high Z atoms of nanoparticles are the major players in the extra dose delivered around the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Several nanoparticles have been used and studied for application in nanoparticle-aided radiation therapy (NART) with the photons in the energy range of tens to hundreds of keV. 2,5,[11][12][13][14][15][16][17] The studies showed that photoelectrons produced through photoelectric interaction of photons with high Z atoms of nanoparticles are the major players in the extra dose delivered around the nanoparticles. 15,18 However, after the photoelectric phenomenon, in addition to photoelectrons, the auger electrons, characteristics x-rays, other secondary electrons are released from nanoparticles and deliver a high dose near the surface of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%